Wild Pedagogies in Practice: Inspiration for Higher Education - Reineke Susan van Tol; Arjen Wals (Australian Journal of Environmental Education)
Wild pedagogies (WP) are emerging as critical, relational alternative to current, often unsustainable learning practices. WP aim to offer a way of learning in, with, through and for nature, embracing a post-humanist, relational perspective. So far, WP have mainly been explored theoretically. Increasingly, educators both within and outside of formal education, are inspired and apply WP in their education. Throughout the world, examples of learning that fit into WPs’ living definition, are emerging. However, concrete inspiration for how to bring WP theory into practice, is still largely lacking. In this paper, we explore three emerging approaches at Wageningen University (The Netherlands), that are inspired by wild pedagogies. Empirically, we combine formative evaluations of course designs with participant observation in a collective case study setting over three years. The empirical research is embedded in an explorative literature review that led us to four explorative areas of WP, namely (1) Wild and caring learning spaces (2) Learning from self-will and wonder (3) Relational learning with the world and (4) Disruptive learning for the world. Eventually we present concrete inspiration on those four areas for implementing WP in formal higher education.